Differentiating segmental contribution of rotational power of the core: Reliability and diagnostic applications - Zois, J.; Fathers, S.; Cronin, J. B. (Journal of Australian Strength and Conditioning, 2018)
Rotary power is an important physical attribute that contributes to sporting movements such as kicking, throwing, punching change-of-direction and agility tasks, hence its assessment is of interest to practitioners. This study investigated a novel method for assessing multi-segmental rotary power, variables of interest were the variability and power outputs associated with each of the segmental contributions. Fifteen semi-elite participants performed three rotational assessments on a KIESER functional trainer separated by seven days, implementing four different movements: Stage 1) arm only; Stage 2) arm and trunk; Stage 3) arm, trunk and legs - concentric; and, Stage 4) arm, trunk and leg-countermovement. The difference between left and right sides for each of the movements (stages) ranged from 7 to 11% (p > 0.05). The coefficient of variation (CV) over the three test occasions were consistently = 10% with the exception of the Stage 1 (12.3%). The intraclass correlation coefficients were strong to nearly perfect; seven of the eight comparisons greater than 0.90. The only stages that were not significantly (p > 0.05) different to each other were Stages 2 and 3 (Stage 1= 356 W; Stage 2= 445 W; Stage 3=464 W; Stage 4=519W {p<0.05}). Increasing segmental contribution during a novel rotary power assessment task enhanced power output by almost 35% (stage 1-4). This research provides practitioners with a reliable method to assess rotary power in athletes and a foundation to identify segmental differences and/or energy leakage when the movement is interpreted as a sum of its parts.